Building the Education Outcomes Linkage (EOL) 2018/19-2021/22 - Northern Ireland - McCullough, Nichola; Norris, Eoin; McAlister, Megan; Dunlop, Shauna (International Journal of Population Data Science, 2025)
Objectives To produce an annonymised research ready longitudinal relational database of schools’ data for pupils aged 14 and over in Northern Ireland to be used to inform policy development and evaluation and increase knowledge of the factors that influence educational achievements and post 16 pathways chosen by young people. Methods The data for the EOL was drawn from databases held by the Department of Education in Northern Ireland. These include the school census (including attendance data); the school leavers survey; and the exams database all of which were linked by an annonymised ID. The school census and exams database acted as the spine for linkage. Only pupils present in both the school census in at least one of the academic years 2018/19 - 2021/22, and with an exam outcome for the corresponding year(s), are included in the EOL. Where available/applicable attendance and school leavers data were linked to the spine. Results Our linkage criteria produced a final dataset for n=122,273 unique individuals covering four academic years, including the period of exposure to Covid-19. We will report the number of records in each database, along with the approaches undertaken to prepare the data for linkage, the issues encountered and how these were resolved. We will give an overview of the Quality Assurance approach we undertook to ensure the data was accurate, reliable and representative. We will demonstrate the guidance document for researchers which includes information on the data sources that contribute to the EOL, descriptions of the variables and caveats that are essential for the understanding of the EOL structure and sample. We will provide step by step guidance on how to access the EOL. Conclusion The EOL dataset was released in November 2024 as a flagship dataset, accessible through the NISRA Secure Environment or the ONS Secure Research Service. We will discuss the current and potential use of the EOL, and its value in understanding and enhancing educational and employment outcomes over time.